KUSALA DHARMA: CONCEPTUAL METAPHOR THROUGH A PERSPECTIVE OF PHRA BRAHMAGUNABHORN - Srinamkam, Kritsada; Mudjalin (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2023)
This article presents an analytic study on the metaphor expressions and conceptual metaphor of Kusala Dharma in the Buddhist writings, a set of the 46 recommended Buddhist writings for Buddhist, by Phra Brahmagunabhorn on a website: www.book.watnyanaves.net. The study outcome highlighted 62 metaphoric expressions that could be classified into 9 conceptual metaphors. The most distinguished ones were Kusala Dharma is Journey followed by Kusala Dharma is Liberation, Kusala Dharma is Cleaning, Kusala Dharma is Remedy, Kusala Dharma is Lighting], Kusala Dharma is Eating, Kusala Dharma is Heat Relief, and Kusala Dharma is War]; the least distinguished was Kusala Dharma is Planting. According to his personal concept or experience, Phra Brahmagunabhorn compared these 9 conceptual metaphors of Kusala to 9 types of activity or incident in human’s daily life.